"(...), the more intense the dialogue and exchange between coach and medical staff, the more benefit for athlete support quality!" - Annika Steinmann; Moritz Breucker; Anna Klees; Milena Pippert; David Jaitner; Swen Körner (Bern Open Publishing, 2023)
Background According to key assumptions to modern systems theory (Luhmann, 1983, 1990) the individual action logic of both sports coaches and sports physiotherapists are likely to differ fundamentally. Although both professions are entrusted with the care of athletes, they each follow different systemic logics in doing so. While coaches are embedded in the elite sport system, sports physiotherapists are assigned to the health care system Steinmann et al., 2019). The professional action of both players follows different systemic expectations in each case. Research Question What are potential conflicts within the cooperation between sports physiotherapists and coaches and what are areas of improvement? Methods The project aims at transferring research into practice and includes two parts: First, the project-team performs guided expert interviews with sports physiotherapists (n = 27) and coaches (n = 20) working in German elite sport in order to gather mutual functional, role and action expectations in real social situations. These expectations are compared and fitted in professional theory. The evaluation is based on qualitative content analysis (Kuckartz & Rädiker, 2020; Mayring, 2015). The second part of the project contains a Delphi-Workshop (Niederberger & Renn, 2018). Contentious results are phrased in a rating form for the participants a) to discuss and b) to derive recommended courses of action and case studies. Results Information gathering, content analysis and results are completed. Furthermore, the Delphi-Workshop took place in September 2022 (n = 8). The assumption has been confirmed that potential for optimization of the cooperation between coaches and sports physiotherapists is above all found in their structurally different action logic. The interview partners agree that there is a lack of financial reward for physiotherapists and therefore question international competitive ability. Conflicts are often found in the process of Return-to-Sport decision making since coaches are members of the elite sports system whereas physiotherapists belong to the health system. Furthermore, different employment models can lead to different engagement, because coaches in elite sports usually have a permanent position whereas physiotherapists usually work as freelancers for a low fee. Conclusion By delivering qualitative-empiric insight into the cooperation between coaches and sports physiotherapists in German elite sports, the project identifies starting points for its further improvement. Results verify the need for further research and relevance for the elite sports system. Recommended plans of action and case studies will be provided to organizations in elite sports and to the project's cooperation partners. References Kuckartz, U., & Rädiker, S. (2020). Fokussierte Interviewanalyse mit MAXQDA, Schritt für Schritt [Focused interview analysis with MAXQDA, step by step]. Springer. https://doi.org/10.1007/978-3-658-31468-2 Luhmann, N. (1983). Medizin und Gesellschaftstheorie [Medicine and social theory]. Medizin, Mensch, Gesellschaft, 8, 168-175. Luhmann, N. (1990). Soziologische Aufklärung 5: Konstruktivistische Perspektiven [Sociological enlightenment 5: Constructivist perspectives]. VS Verlag für Sozialwissenschaften. https://doi.org/10.1007/978-3-322-97005-3_8 Mayring, P. (2015). Qualitative Inhaltsanalyse: Grundlagen und Techniken [Qualitative content analysis: Basics and techniques] (12th ed.). Beltz Pädagogik. Niederberger, M., & Renn, O. (2018). Das Gruppendelphi-Verfahren: Vom Konzept bis zur Anwendung [The Group Delphi Process: From concept to application ]. Springer VS. https://doi.org/10.1007/978-3-658-18755-2 Steinmann, A., Jaitner, D., & Himmelseher, N. (2019). "One aspect of the coaching business." Function and role of sports physiotherapists from the perspective of coaches in German elite athletics. Sports Coaching Review, 9(3), 253-272. https://doi.org/10.1080/21640629.2019.1657680